2014
DOI: 10.1590/1415-52732014000300007
|View full text |Cite
|
Sign up to set email alerts
|

Reference serving sizes for the Brazilian population: An analysis of processed food labels

Abstract: OBJECTIVE: To compare serving sizes reported on processed food labels with reference serving sizes according to nutrition labeling legislation and the "Food Guide for the Brazilian Population". METHODS: This cross-sectional study analyzed the labels of 2,072 processed foods in a supermarket of Florianópolis, Santa Caratina, Brazil. The foods were classified according to the Brazilian food labeling legislation. Central tendency and variability values were calculated for the serving sizes and energy values repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
0
12
0
2
Order By: Relevance
“…However, research also emphasizes that it is essential to teach Brazilians on how to interpret nutrition labels so that this information can play a role in facilitating healthy food choices 33 . A recent study has also emphasized the need for updating the reference energy density used to calculate the recommended serving sizes per food product for the Brazilian nutrition labeling law 14 . This study analyzed 2,072 food products available in Brazil and found that the average energy density reported on these foods differed from the reference energy density used for calculating the recommended serving sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research also emphasizes that it is essential to teach Brazilians on how to interpret nutrition labels so that this information can play a role in facilitating healthy food choices 33 . A recent study has also emphasized the need for updating the reference energy density used to calculate the recommended serving sizes per food product for the Brazilian nutrition labeling law 14 . This study analyzed 2,072 food products available in Brazil and found that the average energy density reported on these foods differed from the reference energy density used for calculating the recommended serving sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that a lack of serving size standardization among similar foods may affect the objectives of nutrition labeling, as it complicates food choices 6,[13][14][15] . Studies have suggested that this lack of serving size standardization may be related to the energy density of processed foods 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Yoghurts and dairy drinks had declared servings varying from 100 to 200 g, even though the serving size recommended by legislation is 200 g. The variation in serving size was greater than that allowed by Brazilian legislation (140–260 g). An even greater variation in serving sizes of dairy products marketed in Brazil was found by Kliemann et al [ 43 ]. The authors analysed serving sizes of all processed and ultraprocessed foods sold in a Brazilian supermarket, totalling 2072 products.…”
Section: Declared Serving Size On Packaged Foodsmentioning
confidence: 97%
“…The authors analysed serving sizes of all processed and ultraprocessed foods sold in a Brazilian supermarket, totalling 2072 products. A great variation in serving size was observed among similar products—the serving sizes of dairy products varied from 75 to 300 g, whereas those of ready-to-eat and semi-ready products varied between 55 and 240 g. This variability may compromise the analysis and the comparison of foods by consumers at the time of purchase [ 43 ].…”
Section: Declared Serving Size On Packaged Foodsmentioning
confidence: 99%
See 1 more Smart Citation